2020
DOI: 10.1021/acs.macromol.0c02224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amorphous Ethylene Copolymers with 2-Vinylnaphthalene, 4-Vinylbiphenyl and 1-(4-Vinylphenyl)naphthalene

Abstract: Ethylene copolymerization with 2-vinylnaphthalene (VN) by ( t BuC 5 H 4 )TiCl 2 (O-2,6-i Pr 2 C 6 H 3 ) (1)−MAO catalyst system afforded high-molecular-weight amorphous copolymers with unimodal molecular weight distributions as well as uniform compositions (M n = 18 100−39 900, M w /M n = 1.23−1.47, T g = 24−75 °C, VN 21.6−44.8 mol %). Copolymerization with 4vinylbiphenyl (VB) using 1− and (1,2,4-Me 3 C 5 H 2 )TiCl 2 (O-2,6-i Pr 2 C 6 H 3 ) (2)−MAO catalyst systems also yielded highmolecular-weight copolymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Table summarizes the results for ethylene copolymerizations with myrcene (My) using various half-titanocene ( 1 – 4 , Chart )–MAO catalyst systems. The phenoxide- or ketimide-modified half-titanocenes shown in Chart , Cp′TiCl 2 (O-2,6- i Pr 2 -4-RC 6 H 2 ) [R = H, Cp′ = Cp* ( 1 ), t BuC 5 H 4 ( 3 ); R = SiEt 3 , Cp′ = Cp* ( 2 )] and CpTiCl 2 (N = C t Bu 2 ) ( 4 ), have been chosen in this study because these catalysts demonstrated efficient comonomer incorporations in the ethylene copolymerizations with sterically encumbered olefins, , cyclic olefins, and aromatic vinyl monomers. , An AlMe 3 -free MAO white solid, which was prepared from the commercially available MAO sample [8.9 wt % (Al) toluene solution, see the Experimental Section] by removing toluene and AlMe 3 in vacuo , , , was used as the cocatalyst. The results by the ordinary linked-amide half-titanocene, [Me 2 Si­(C 5 Me 4 )­(N t Bu)]­TiCl 2 ( 5 ), , and the metallocene catalyst, Cp 2 ZrCl 2 ( 6 ), conducted under the same conditions are also placed for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table summarizes the results for ethylene copolymerizations with myrcene (My) using various half-titanocene ( 1 – 4 , Chart )–MAO catalyst systems. The phenoxide- or ketimide-modified half-titanocenes shown in Chart , Cp′TiCl 2 (O-2,6- i Pr 2 -4-RC 6 H 2 ) [R = H, Cp′ = Cp* ( 1 ), t BuC 5 H 4 ( 3 ); R = SiEt 3 , Cp′ = Cp* ( 2 )] and CpTiCl 2 (N = C t Bu 2 ) ( 4 ), have been chosen in this study because these catalysts demonstrated efficient comonomer incorporations in the ethylene copolymerizations with sterically encumbered olefins, , cyclic olefins, and aromatic vinyl monomers. , An AlMe 3 -free MAO white solid, which was prepared from the commercially available MAO sample [8.9 wt % (Al) toluene solution, see the Experimental Section] by removing toluene and AlMe 3 in vacuo , , , was used as the cocatalyst. The results by the ordinary linked-amide half-titanocene, [Me 2 Si­(C 5 Me 4 )­(N t Bu)]­TiCl 2 ( 5 ), , and the metallocene catalyst, Cp 2 ZrCl 2 ( 6 ), conducted under the same conditions are also placed for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The linked half-titanocene ( 5 ) showed rather low catalytic activity than the phenoxide-modified catalysts ( 1 , 2 ), and the resultant polymer possessed a rather high T m value (108 °C, run 8) compared to those prepared using 1 and 2 ( T m = 59.5–60.5 °C, runs 2–5), suggesting that 5 showed less My incorporation than 1 and 2 . It was also revealed that MAO itself gave a low molecular weight polymer ( M n = 2200, run 1), probably via a cationic manner in small amounts, , but attempts for separation by extracting the homopolymer with acetone through centrifugation , generally gave a tiny trace (negligible) amount of polymer collected as an acetone soluble fraction. Due to low polymer yield (run 8), it seemed difficult to separate poly­(My) formed by MAO itself, as described below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations